KELUARGA SEBAGAI LEMBAGA PENDIDIK PERTAMA DAN UTAMA: STUDI KITAB ULANGAN 6:1-9 - Janse Belandina Non-Serrano (Regula Fidei: Jurnal Pendidikan Agama Kristen, 2016)
The experience during their childhood is a very important factor in the next development phase of children’s life. One of the most significant forms of the experience is parental exemplary, an influential means of faith and moral education for children. Proper parental exemplary will make children responsible, possess good attitude and healthy social relationships, and have a good religiosity. God commands parents to educate their children to know and love Him. This indicates that parents—the leaders in the family—should carry out God’ mandate commanding them to be the first and primary educator for their children. The education provided by parents is through verbal teachings and exemplary through real daily activities. Only parents who know God and who keep closely associating with Him through prayer and reading the Bible will be resilient and able to educate their children on the right path and in the will of God. Every parent is obligated to train their children in the womb. Childhood is an important period for imparting integral education. Abstraks: Pengalaman masa kanak-kanak merupakan faktor yang sangat penting bagi perkembangan anak selanjutnya. Keteladanan orang tua menjadi wahana pendidikan iman dan moral bagi anak, membentuk anak sebagai makhluk individu yang bertanggung jawab, memiliki sikap dan hubungan sosial yang sehat, memiliki religiusitas yang baik. Allah memberikan tugas pada orang tua untuk mendidik anak-anaknya mengenal dan mengasihi Allah. Itu berarti, orang tua sebagai pemimpin dalam keluarga yang mengemban amanah dari Allah untuk menjadi pendidik pertama dan utama bagi anak-anaknya. Bentuk pendidikan yang diberikan oleh orang tua adalah melalui ajaran verbal dan keteladan hidup melalui perbuatan nyata yang patut diteladani. Hanya orang tua yang mengenal Allah, bergaul erat dengan Allah melalui kesetiaan berdoa dan membaca Alkitab yang akan tabah dan mampu mendidik anak-anaknya di jalan yang benar dan dikehendaki Allah. Setiap orang tua berkewajiban mendidik anak-anaknya sejak dalam kandungan. Masa kanak-kanak merupakan masa yang penting dalam menanamkan pendidikan yang bersifat integral.